Characteristics of Teachers’ Mattering by Demographic Variables - Budreikaitė, Justina; Raišienė, Agota Giedrė (Pedagogika, 2025)
The teaching profession is linked to stress and anxiety, yet it also involves a sense of meaningful work and interpersonal relationships. Job satisfaction among teachers is closely tied to a sentiment that their work matters to society. This exploratory study examines demographic differences in mattering perceptions of teachers. Mattering describes the human need to feel important and significant to others. In organizations, mattering enhances employee well being, engagement, performance, and motivation, workplace relationships, and commitment. Addressing mattering can offer insights into improving teachers’ wellbeing and job satisfaction; however, very few studies seek to evaluate demographic differences in mattering perceptions. Thus, this paper aims to investigate demographic characteristics of mattering among teachers. The results indicate mattering perceptions vary based on respondents’ age, gender, and work position. Work experience and individual needs did not show statistically significant differences, which may coincide with agerelated differences or indicate low perceptions of career options available. Despite limitations in generalizability due to sample distribution and size, the study provides practical implications. Customizing motivational initiatives based on demographic differences may help improve organizational culture and inclusivity and tailor them to suit teachers’ preferences and needs better.